2022
DOI: 10.1007/s11121-022-01387-z
|View full text |Cite
|
Sign up to set email alerts
|

What Works for Whom in School-Based Anti-bullying Interventions? An Individual Participant Data Meta-analysis

Abstract: The prevalence of bullying worldwide is high (UNESCO, 2018). Over the past decades, many anti-bullying interventions have been developed to remediate this problem. However, we lack insight into for whom these interventions work and what individual intervention components drive the total intervention effects. We conducted a large-scale individual participant data (IPD) meta-analysis using data from 39,793 children and adolescents aged five to 20 years (Mage = 12.58, SD = 2.34) who had participated in quasi-expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The likelihood that the intervention would fail increased as the students got older. This finding is consistent with the results of Johander et al (2021) who found that targeted interventions were less effective in secondary schools compared to primary schools, as well as meta-analyses indicating that whole-school antibullying programs tend to work better among younger students (e.g., Hensums et al, 2022;Yeager et al, 2015). According to the present findings, however, it is not only a matter of primary schools having a greater capacity than secondary schools for dealing with bullying, but of developmental differences as well; every additional year made the intervention failure more likely.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The likelihood that the intervention would fail increased as the students got older. This finding is consistent with the results of Johander et al (2021) who found that targeted interventions were less effective in secondary schools compared to primary schools, as well as meta-analyses indicating that whole-school antibullying programs tend to work better among younger students (e.g., Hensums et al, 2022;Yeager et al, 2015). According to the present findings, however, it is not only a matter of primary schools having a greater capacity than secondary schools for dealing with bullying, but of developmental differences as well; every additional year made the intervention failure more likely.…”
Section: Discussionsupporting
confidence: 89%
“…The age of the students involved appears to play a role in how successful adult interventions are at stopping bullying and therefore victimization. Previous research has shown that both whole-school antibullying programs (Hensums et al, 2022;Yeager et al, 2015) and targeted interventions specifically (Johander et al, 2021) tend to be less effective in adolescence than in childhood. In addition, the intensity of the victimization or bullying (how often it happens, how long it has been taking place) might make interventions less likely to succeed.…”
Section: Factors Associated With Intervention Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if teenagers have positive feelings towards themselves, such as feeling like they have high self-esteem are competent and attractive and get the necessary physical support, teenagers can avoid bullying victimisation that can occur. 57 Friendship quality is an effective factor in preventing peer victimisation, such as high quality friendships. 58 Adolescents who have high levels of support from their friends have lower levels of bullying and victimisation.…”
Section: Conclusion Acknowledgement Ethicsmentioning
confidence: 99%
“…Finally, the effectiveness of different components is likely to depend on the age of the students to whom they are applied (e.g., elementary vs. middle school students) (Yeager et al, 2015). Indeed, some recent meta-analyses have tried to ascertain not only which components are effective, but specifically for whom (Hensums et al, 2022). Even so, it is indisputable that the promotion of bystander intervention is at the core of programs that currently have the greatest effectiveness (e.g., the KiVa program) (Sainio et al, 2020; Salmivalli et al, 2021).…”
Section: The Prevention Of Bullying At Schoolsmentioning
confidence: 99%